Pola Jaringan Komunikasi Organisasi dalam Memperkuat Relasi Antarpribadi dan Kinerja di Paguyuban Kange Yune Bojonegoro (PKYB) - Muhammad Krisna Rachmatullah; Sintya Verawati Siahaan; Lisa Safira; Rijal Padlilah; Nanda Tasya Rizkie Ekaputri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Paguyuban Kange Yune Bojonegoro (PKYB), a youth organization in Bojonegoro Regency, implements an informal, family-based communication system. This study analyzes PKYB's communication network patterns in building interpersonal relationships and organizational performance. Through a qualitative approach using interviews and literature review, it was found that PKYB applies diagonal and horizontal communication patterns allowing multidirectional information flow. This system strengthens interpersonal relationships and member participation, but potentially leads to information inconsistency. PKYB successfully adopts an adaptive open system, despite facing challenges in information verification and validation. These findings highlight the importance of balancing communication flexibility and formal structure to enhance the effectiveness of community-based organizations.